The body in poverty - Psalm 22 - Zwan, Pieter van der (Journal for Semitics, 2017)
The bodily suffering in this psalm can be related to a socio-economic situation of poverty. In addition, it is also closely linked to an experience of distance from God and the community of belonging with its terrible emotional consequences. Although the direction of causality is unclear it would seem that the body breaks down when the solitary self feels alienated from God and from corporate belonging. The description of bodily parts in this psalm therefore contains various layers of meaning beyond the physical, including simultaneously the psychological, social, and spiritual.
free